2017
DOI: 10.1061/(asce)gt.1943-5606.0001645
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Shear-Wave Velocity and Geotechnical Parameters for Norwegian Clays

Abstract: A database of shear-wave velocity (V s) measurements using a variety of techniques and soil properties measured on high-quality samples for 28 Norwegian sites has been established. The purpose was to evaluate the different methods of measuring V s , to present guidelines and correlations to assist in estimating V s profiles in these clays in the absence of site-specific data, and to outline relationships that can be used to give first-order estimates of soil properties. It was found that consistent measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…From an extensive study of Norwegian clays, [22] showed that 'p correlated well with the square of the shear wave velocity, Vs 2 , with the coefficient of variance R 2 being 0.80. Thus, 'p correlates well with Gmax.…”
Section: Why Is Gmax a Function Of 'P?mentioning
confidence: 99%
See 1 more Smart Citation
“…From an extensive study of Norwegian clays, [22] showed that 'p correlated well with the square of the shear wave velocity, Vs 2 , with the coefficient of variance R 2 being 0.80. Thus, 'p correlates well with Gmax.…”
Section: Why Is Gmax a Function Of 'P?mentioning
confidence: 99%
“…Some researchers have attempted to provide a unifying framework pertaining to the evaluation of Gmax of clays ([20] - [22]). However, it is quite challenging to propose a framework that considers all the abovementioned factors.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between the pressure wave velocity and applied density is depicted in figure 14. By following formula, the density can be calculated according to the velocity of pressure wave, in following equation, if density is denoted by ρ (in g/cm 3 ) and pressure wave velocity (v p ) is in m/s, the value of a will be considered 0.31 [25,26]. …”
Section: The Relationship Between Density and Condensation Velocitymentioning
confidence: 99%
“…The target of this study is to obtain change of attenuation and velocity of the waves to know subsurface structures. Pressure and shear wave velocity were calculated in the study boreholes and consequent catch geotechnical parameters [3], [4]. These parameters have extensive application and important in the engineering tasks.…”
Section: Introductionmentioning
confidence: 99%
“…When more advanced inversion techniques are used and S‐wave velocity is derived, this offers a direct dependence on various basic geotechnical strength/stiffness parameters (e.g., undrained shear strength and plasticity index) through the shear modulus. Although there are no published soil mechanical relationships, there are numerous empirically derived relationships based on terrestrial studies (e.g., L’Heureux and Long ) and some with marine sediments (Ayres and Theilen ).…”
Section: Integrated Frameworkmentioning
confidence: 99%